STUDY ON NEUTRON – GAMMA PULSE SHAPE DISCRIMINATION ALGORITHMS FOR SCINTILLATION DETECTOR - Phan Văn Chuân; Nguyễn Đức Hòa; Nguyễn Đắc Châu; Vương Nữ Minh Khuê (Tạp chí Khoa học Đại học Đà Lạt)
The four neutron - gamma pulsed shape discrimination algorithms for the model NE213 scintillation detector by using digital signal processing were developed. In this study, a pulse generator, pulse digitizer and neutron - gamma pulsed shape discrimination algorithms are simulated in Matlab, Simulink software. The results obtained show that the method to rise-time discrimination has a quality factor (Figure-of-Merits: FOM=1.09), pulsed gradient analysis method (FOM = 0.66), charge comparison method (FOM = 2.21), and correlation pattern method (FOM = 1.97). This result is the basis for building systems for measurements of neutron using scintillation detectors.